English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(7x+5y+2)*(2x-3y+7)? is x times a y xy? i got through it but my answer has 11xy and -11xysquared in part of it.my whole answer is 14xsquared-11xy-11xysquared+29y+14. is this right?

2007-05-27 15:17:06 · 11 answers · asked by tries to understand why/how 3 in Science & Mathematics Mathematics

11 answers

14x^2 - 14xy + 49x + 10xy - 15y^2 + 35y + 4x - 6y + 14

14x^2 - 11xy + 53x + 29y - 15y^2 + 14

2007-05-27 15:24:18 · answer #1 · answered by Anonymous · 0 0

(7x+5y+2)*(2x-3y+7)
= [7x(2x-3y+7) + 5y(2x-3y+7) + 2(2x-3y+7)]
= [(14xsq - 21xy+ 49x) + (10xy - 15ysq + 35y) + (4x - 6y + 14)]
= 14xsq - 15ysq - 21xy + 10xy + 49x + 4x + 35y - 6y + 14
= 14xsq - 15ysq - 11xy + 53x + 29y + 14

As you can see, the first step is to break up the elements and times 7x with the next whole equation, add 5y times the next equation and finish off with 2 times the next equation.

Then merely arrange the elements by their letters and add and subtract accordingly.

This is what you'll get in the end. No xy squared if you look carefully.

2007-05-27 15:31:16 · answer #2 · answered by Studier Alpha 3 · 0 0

14 x squared - 15 y squared - 11xy + 53x + 29y + 14

2007-05-27 15:22:01 · answer #3 · answered by discopuppy 2 · 0 0

14x squared + 53x - 11xy + 29y + 14x squared + 14

2007-05-27 15:26:23 · answer #4 · answered by princess 2 · 0 0

yes, x*y = xy

as for the whole thing, just break it into pieces:

7x*(2x-3y+7) =14x^2 - 21xy + 49x
5y*(2x-3y+7) = ----------10xy + ------ -15y^2 + 35y
2*(2x-3y+7) = ---------------------- 4x + ---------- - 6y + 14
which gives: 14x^2 - 11xy + 53x - 15y^2 + 29y + 14

(sorry about all the dashes, it doesn't seem to be able to deal with spaces...)

2007-05-27 15:31:32 · answer #5 · answered by Anonymous · 0 0

If you're simplifying

You should get...

14xsquared +49x+35y+4x-6y+14

Simplify...

14xsquared-15ysquared-11xy
+53x+29y+14

I think this is it...

2007-05-27 15:28:47 · answer #6 · answered by Phyllis M 2 · 0 0

Multiply 2 to 3x+3y+2z=-3 so this is going to grow to be 6x+6y+4z=-6 you could now use eliminating (remove z) 5x-2y-4z=-3 + 6x+6y+4z=-6 -------------------------- 11x+4y= -3 Multiply 3 to 3x + 3y + 2z = -3 so this is going to grow to be 9x+9y+6z= -9 Multiply 2 to -2x+5y+3z=3 so this is going to grow to be -4x+10y+6z=6 I did this so that you'll remove z decrease back 9x+9y+6z= -9 - -4x+10y+6z= 6 --------------------------- 13x -y = -15 you on the instantaneous have 2 equations 13x - y = -15 ----a 11x + 4y = -3 ----b Isolate y in equation a and change it to equation b y = 13x + 15 11x + 4(13x+15) = -3 11x + 52x +60 = -3 63x = -sixty 3 x= -a million change this to equation a y = 13(-a million) +15 y= 2 change the values of x and y to -2x + 5y +3z=3 -2(-a million) + 5(2) + 3z =3 2 + 10 + 3z =3 12 + 3z =3 3z = -9 z = -3 consequently, x =-a million y=2 z= -3 to substantiate the options, change this values to those 3 equations and the equation might want to need to be surely :D want this allows :D

2016-11-28 02:35:35 · answer #7 · answered by ? 3 · 0 0

(7x+5y+2)*(2x-3y+7)
=(7x)(2x)+(7x)(-3y)+(7x)(7)+(5y)(2x)+(5y)(-3y)+(5y)(7)+(2)(2x)+(2)(-3y)+(2)(7) [applying distributive law]
=14x^2-21xy+49x+10xy-15y^2+35y+4x-6y+14
=14x^2-11xy+53x+29y+14-15y^2

2007-05-27 15:29:32 · answer #8 · answered by ghost whisperer 3 · 0 0

i think your answer is wrong

(7x+5y+2)*(2x-3y+7)?
=(14x^2-21xy+49x+10xy-15y^2+35y+4x-6y+14)
=14x^2-15y^2-11xy+53x29y+14

2007-05-27 15:26:08 · answer #9 · answered by jackleynpoll 3 · 0 0

That is the mathematical equation on how to make a grilled cheese sandwich, with just a litttllee extra cheese.

2007-05-27 15:19:53 · answer #10 · answered by Oh, Natey-O! 3 · 0 0

fedest.com, questions and answers